Analisis Partisipasi Angkatan Kerja Perempuan di Indonesia - Koto, Rahmawati; Ridwan, Endrizal; Muharja, Fajri (Jurnal Informatika Ekonomi Bisnis, 2025)
This study analyzes the influence of education level, training, place of residence, and work experience on female labor force participation. The objective of this research is to determine the effect of education level, training, place of residence, and work experience on female labor force participation and to identify the most dominant factor influencing female labor force participation in Indonesia. The sample used in this study consists of 393,359 individuals, representing female labor force participants in 2021. The research method employed is logistic regression. The results show that education level, training, and work experience have a positive and significant effect on female labor force participation, while place of residence has a negative and significant effect. The most dominant factor is education.